Optical characterisation of Steatoda paykulliana spider dragline silk - Ganesan, Sathiyapriya (2021)
This project aims to characterise the optical properties of spider silk under the non-destructive light microscopy technique. Spider silk is of interest to the bioengineering and industrial communities because of its mechanical and biomedical properties, such as being extremely strong, flexible and light conductive. Polarised light microscopy is a contrast enhancing technique used to quantify the optical properties of the birefringent materials. Using this method, the composition and three-dimensional structure of the anisotropic crystals can be investigated. Since spider silk is an anisotropic material, the optical properties of the silk and in particular the birefringence of the spider silk was measured using this technique. Initially, a simple optical microscope was constructed using Thorlabs components in order to evaluate the birefringence of the Steatoda spider silk. Subsequently it was found that, the measurement of birefringence could not be calculated and the assembled system was not appropriate, as the silk indulged with different hydration conditions. Hence the optical properties of Steatoda spider silk under different environmental conditions were evaluated using the Olympus BX51 polarised light microscope. The research data acquired from the experiment were analysed using the statistical method. From the analysis, the proposed hypotheses were proved. such as significant difference in the value of birefringence within individual sample and between discrete silk samples. Also, substantial variance in thickness within individual silk sample and between distinct silk samples. Finally using data analysis, the value of birefringence under four different conditions were analysed and it indicated that the value of birefringence was varied to a great extent – it had a maximum value when the silk was in dry condition, the value decreased when the silk was in hydration; during dehydration the value increased again and in supercontraction, the value was drastically decreased. This is due to the fact that different environmental conditions affect the molecular assembly of the silk and this will possibly affect the properties of the silk.